Development of Google Sites-Based Learning Media Using the Merdeka Approach to Increase Interest in Learning Pancasila Education Among Seventh Grade Students at SMP Negeri 21 in South Tangerang City - Shella Rachmawaty; Sri Rahayu Pudji Astuti; Suidat (JOCER: Journal of Civic Education Research, 2025)
Pancasila Education is essential for shaping students’ civic responsibility and national identity; however, at SMP Negeri 21 in South Tangerang City, preliminary observations indicate that only 35% of seventh-grade students actively engage in learning, with most relying on rote memorization due to conventional teacher-centered methods. Previous studies have suggested the potential of Google Sites as an interactive medium to enhance students’ motivation, but its application in combination with the Merdeka learning approach in Pancasila Education has not been sufficiently explored. Previous studies have suggested the potential of Google Sites as an interactive medium to enhance students’ motivation, but its integration with the Merdeka approach in Pancasila Education remains underexplored. This study aimed to develop and evaluate Google Sites-based learning media using the Merdeka approach to improve seventh-grade students’ learning interest at SMP Negeri 21 South Tangerang City. Employing a Research and Development (R&D) design with the ADDIE model, the study involved expert validation and classroom implementation. The validation results indicated significant improvement after revisions: media experts rated 94.04% (very feasible), material experts 92.8% (very feasible), and language experts 94.4% (very feasible). Pre-implementation surveys showed students’ learning interest was categorized as “weak” with an average score of 35.2%, reflecting low enjoyment, limited engagement, and lack of motivation. After implementing the developed media, the score increased to 71.7%, classified as “strong,” with consistent improvement across indicators such as enjoyment, interest, acceptance of peers’ opinions, and active participation. These findings highlight that Google Sites-based media not only enhanced visual appeal but also fostered participatory, contextual, and meaningful learning experiences through interactive features like videos, quizzes, and reflective activities. It can be concluded that the developed media is effective and feasible for enhancing students’ learning interest in Pancasila Education and provides practical implications for fostering digital and character-based learning in junior secondary schools.